The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12185-011-0825-8
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B12 deficiency, hyperhomocysteinemia and thrombosis: a case and control study

Abstract: This study aimed at assessing the relationship between thrombosis, hyperhomocysteinemia and vitamin B12 deficiency using a case-control study carried out in 326 patients with thrombosis (case group) and 351 patients from the same hospital (control group). Apart from the classic risk factors, a number of hematological variables were evaluated, including serum vitamin B12 (B12), red cell folate (RCF), and serum homocysteine (Hcy). An evaluation of serum methylmalonic acid (MMA) and a clinical study were carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 51 publications
(79 reference statements)
2
34
1
1
Order By: Relevance
“…7 As expected, patients with thrombosis showed a significantly increased proportion of hyperhomocysteinaemia and low B12 levels. 7 Another interesting element of our case presentation is the slightly increased haematocrit, detected in a nonsmoker with chronic kidney disease and without evidence of hypoxia. Due to persistently increased haematocrit during and after his hospitalisation, further testing was performed.…”
Section: Letters To the Editorsupporting
confidence: 62%
“…7 As expected, patients with thrombosis showed a significantly increased proportion of hyperhomocysteinaemia and low B12 levels. 7 Another interesting element of our case presentation is the slightly increased haematocrit, detected in a nonsmoker with chronic kidney disease and without evidence of hypoxia. Due to persistently increased haematocrit during and after his hospitalisation, further testing was performed.…”
Section: Letters To the Editorsupporting
confidence: 62%
“…Metabolomic analysis showed that, compared to CF rats, MR rats had significantly lower levels of 5MeTHF and pyridoxal (vitamin B6). These are important co-factors in the conversion of homocysteine to methionine and cystathionine, and deficiencies of these two molecules are well documented to increase plasma homocysteine levels [56,57,58]. Because supplementation of the MR diet with cysteine restored homocysteine to control levels and increased levels of 5MeTHF and vitamin B6 but not of CBS protein in the liver, it could be argued that the changes in the bioavailability of these co-factors are contributing significantly to the hyperhomocysteinemic phenotype of MR rats as proposed by Gürdöl [59].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of vitamin B 12 deficiency was based on low serum vitamin B 12 levels (Ͻ200 pg/mL). 17 The serum homocysteine level was measured by an enzymatic method. 18 Routine hematologic examinations that included hemoglobin levels and red cell mean corpuscular volume were also performed.…”
Section: Clinical Assessmentmentioning
confidence: 99%